THE EFFECT OF EDUCATION GIVEN TO HEMODIALYSIS PATIENTS ON SELF-CARE AGENCY AND FLUID CONTROL: A RANDOMIZED CONTROLLED TRIAL - Zeynep Yılmaz; Mağfiret Kara Kaşıkçı; Fatmanur İrgin (Karya Journal of Health Science, 2026)
Objective: This study investigated the effects of education on hemodialysis management provided to patients receiving hemodialysis treatment on self-care agency and fluid control.Method: The study was conducted using a randomized controlled experimental design. Participants receiving hemodialysis treatment were divided into two groups: the intervention group (n=26) and the control group (n=28). Data were collected using the Descriptive Information Form, Self-Care Agency Scale, and Fluid Control in Hemodialysis Patients Scale. The intervention group received individualized education based on the educational booklet entitled “Living with Hemodialysis,” followed by weekly telephone follow-up for seven weeks. Patients in the control group received standard nursing care in accordance with the institution’s routine practices. Eight weeks after the pre-test, the measurement tools were re-administered to both groups. The study was conducted in accordance with the CONSORT guidelines for reporting randomized controlled clinical trials.Results: The post-test scores of the Fluid Control in Hemodialysis Patients Scale were significantly higher than the pre-test scores in both the intervention and control groups. The frequency of hemodialysis significantly decreased following the education in the intervention group, and the post-test frequency of hemodialysis was significantly lower than that of the control group. Self-care agency increased significantly in the intervention group; however, no significant difference was found between the groups in post-test self-care agency. A significant increase in self-care agency from pre-test to post-test was also observed in the control group.Conclusion: Structured education on hemodialysis management improved fluid control and reduced the frequency of hemodialysis in the intervention group. Although self-care agency increased significantly in the intervention group, no significant difference was found between the groups in post-test self-care agency. The integration of structured hemodialysis education into routine nursing care in an effective and sustainable manner recommended to support self-management and fluid control among patients receiving hemodialysis treatment.